Efektivitas Rebusan Daun Kelor Untuk Menurunkan Kadar Gula Darah Pada Pasien DM Tipe II di Wilayah Kerja UPT Puskesmas Tanjung Morawa Tahun 2022 - Peringati Waruwu; Cristine Welga; Melati Hutagalung; Yemima Sahputri Nadeak; Eva Nurzannah Hutabarat; Karmila Br Kaban (Jurnal Multidisiplin Madani, 2022)
Diabetesxmelitus xis a chronicxmetabolic xdisorder with multiple etiologiesxcharacterized by high bloodxsugar levelsxcarbohydrate, lipid and protein. Pharmacologicalxmanagement xuses drugs, while xnon-pharmacological treatmentsxsuch as leaf decoction moringa. Thexpurpose of thisxstudy to determinexthe effectiveness of the consumption of Moringa stew on reducing blood sugar levels in Type II. This type of research pre-e perimental using a onexgroupxpre-test and post-test design plan. The number of respondents is 30 people. The result of the study prove the effectiveness of consuming boiled Moringa leaves (moringa oleifera) in reducing blood sugar levels in patients with type 2 diabetes melitus in the work area of ​the Tanjung Morawa Health Center UPT in 2022 with a p-value of 0,000. In Patient type 2 diabetes melitus at the Tanjung Morawa public health center, it is e pected to be able to utilize natural ingredients. such as Moringa leaves to control blood sugar levels to stay normal.